2013
DOI: 10.5664/jcsm.2748
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polysomnographic and Clinical Presentations and Predictors for Cardiovascular-Related Diseases between Non-Obese and Obese Obstructive Sleep Apnea among Asians

Abstract: Introduction: Unlike Caucasians, many Asians with obstructive sleep apnea (OSA) are non-obese but are affected by the disease due to predisposing craniofacial structure. Therefore, non-obese and obese OSA may represent different disease entities. The associated risk factors for developing cardiovascular-related diseases, consequently, may be considered separately for the two types of OSA. Method: We reviewed polysomnographic studies performed in adults (aged ≥ 18 years) diagnosed with OSA (respiratory disturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 8 publications
(7 reference statements)
1
29
2
Order By: Relevance
“…Another classic symptom of OSA, daytime sleepiness, was not a strong item of the Berlin questionnaire to detect high-risk subjects for OSA (P value 0.059; Table 2) in Thai male subjects. A previous study indicated that Thai male patients with OSA may not have tiredness or daytime sleepiness [7]. Hypertension is known to be associated with OSA [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another classic symptom of OSA, daytime sleepiness, was not a strong item of the Berlin questionnaire to detect high-risk subjects for OSA (P value 0.059; Table 2) in Thai male subjects. A previous study indicated that Thai male patients with OSA may not have tiredness or daytime sleepiness [7]. Hypertension is known to be associated with OSA [13].…”
Section: Discussionmentioning
confidence: 99%
“…Asian OSA patients are different from Western OSA patients in several aspects. Thai OSA patients seemed to be less obese, have fewer symptoms, or have fewer complications [7,8]. The Berlin questionnaire for the Thai population may need some modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was no difference in diagnostic accuracy when using criterion 1 (AHI≥30) or criterion 2 (AHI≥ 40). Several studies have reported racial/ethnic differences in the clinical presentation, sleep study findings, and OSArelated morbidity of OSA [8][9][10][11]. In addition, Asian patients with OSA are reported to be less obese but have a greater OSA severity than Caucasian patients with OSA [8][9][10].…”
Section: Discussionmentioning
confidence: 95%
“…[[41]] Additionally, up to > 60% of patients with a definitive diagnosis of sleep apnoea have been reported to be non-obese. [[42]] Intra-operative events and preventive treatment measures including the application of continuous positive airway pressure (CPAP) used as a ‘pneumatic airway splint’, were not captured. Lack of this information makes it impossible to determine whether this form of treatment modifies the outcome.…”
Section: Discussionmentioning
confidence: 99%